Strategi pembiayaan BPRS dalam meningkatkan pertumbuhan UMKM - Khotimah, Retno Wahyuning Khusnul (Maliki Interdisciplinary Journal, 2024)
Sharia People’s Financing Bank (BPRS) has a crucial role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which often face difficulties in accessing formal financing. BPRS offers a variety of sharia financing products, such as murabahah and musyarakah, which allow MSMEs to get capital without being entangled in interest-bearing debt. With a flexible approach, pick-up services, and business assistance, BPRS not only provides funds, but also helps increase the managerial capacity of MSMEs. Despite facing challenges such as the lack of public understanding of sharia products, BPRS’s commitment to empowering MSMEs contributes to job creation and national economic growth. This article discusses BPRS’s financing strategy in increasing the growth of MSMEs.